SISTEM PAKAR PENUNJANG KEPUTUSAN PENJURUSAN KULIAH BERDASARKAN KEPRIBADIAN DENGAN TEST MMPI 1 DENGAN METODE CERTAINTY FACTOR - Ni Putu Diah Ayu Vita Widia Murti; Chairisni Lubis; Dedi Trisnawarman (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
Personality is the part of every human which is a prominent characteristic of the human person, the whole way a man react and interact with other human beings. Personality is most often described in terms that could be measured properties exhibited by someone. A system designed to help determine personality by Certainty Factor method. Certainty Factor method focuses on the level of confidence. The input of this system is the input value scale of MMPI (Minnesota Multiphasic Personality Inventory) 1 test and process with Certainty Factor that released the results of personality type. The Result of the 120 cases was 82.5% accuracy rate.Key wordscertainty factor, expert system, Minnesota Multiphasic Personality Inventory, personality type